2015
DOI: 10.1111/psyg.12138
|View full text |Cite
|
Sign up to set email alerts
|

Sleep correlates of depression and anxiety in an elderly Asian population

Abstract: Depression and anxiety in a cohort of elderly Asian subjects are associated with a number of sleep-related issues; both are related to a somewhat different profile of sleep problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
84
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 154 publications
(104 citation statements)
references
References 31 publications
14
84
3
3
Order By: Relevance
“…Depression and anxiety are known to be associated with sleep problems (Jansson‐Fröjmark & Lindblom, ; Yu et al, ), and it was important to evaluate if improvement in sleep disturbance was due to improvement in depressive and anxiety symptoms. We found that improvements in sleep disturbance were independent of the improvement in Geriatric Depression Scale and GAI scores.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Depression and anxiety are known to be associated with sleep problems (Jansson‐Fröjmark & Lindblom, ; Yu et al, ), and it was important to evaluate if improvement in sleep disturbance was due to improvement in depressive and anxiety symptoms. We found that improvements in sleep disturbance were independent of the improvement in Geriatric Depression Scale and GAI scores.…”
Section: Discussionmentioning
confidence: 85%
“…This is an interesting finding and may point toward the biologic effects of the relaxation-response elicitation (Bhasin et al, 2013) including changes in energy metabolism and inflammatory responses. Moreover, evidence suggests that mindfulness and tai-chi are beneficial for pain reduction (Yan et al, 2013;Zeidan, Grant, Brown, Mchaffie, & Coghill, 2012) Depression and anxiety are known to be associated with sleep problems (Jansson-Fröjmark & Lindblom, 2008;Yu et al, 2016), and it was important to evaluate if improvement in sleep disturbance was due to improvement in depressive and anxiety symptoms. We found that improvements in sleep disturbance were independent of the improvement in Geriatric Depression Scale and GAI scores.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the variation cannot be attributed purely to differences between ethnic groups, rural and non-rural population, and nursing home and non-nursing home data. A relatively low percentage (15%) of elders has insomnia in the Domkhar valley in India's Ladakh Foley et al 55 23-34% USA Ohayon 56 30% France Maggi et al 57 45% Italy Chiu et al 58 38.2% Hong Kong (Chinese population) Babar et al 59 32.6% Hawaii (Japanese Americans) Kim et al 60 26.4% Japan Pallesen et al 61 38.6% Norway Schubert et al 62 26.4% USA Sukying et al 63 46.3% Thailand Su et al 64 6% Taiwan Yu et al 65 10.4% China Bonanni et al 66 44.2% Italy López-Torres et al 67 36.1% Spain Kim et al 68 29.2% South Korea Li et al 69 49.7% China (rural) Tsou 70 41% Taiwan Ayoub et al 71 33.4% Egypt Ford et al 72 21.3% USA Sagayadevan et al 73 13.7% Singapore (Chinese, Malay, Indian descent) Sakamoto et al 74 15.2% Ladakh, India El-Gilany et al 75 62.1% Egypt (rural) Eser et al 76 60.9% Turkey (nursing home) Makhlouf et al 77 33.4% Egypt (geriatric home) Gambhir et al 78 32% India (hospital) Ogunbode et al 80 27.5% Nigeria (geriatric centre) region, which is at a high altitude of 2900-4200 m. 74 According to some reports, there is a higher prevalence of insomnia in the aged in nursing homes and rural areas. 69,75,76 However, other studies have found no differences in the insomnia patterns of elders in nursing homes and in other homes.…”
Section: Insomnia In the Elderlymentioning
confidence: 99%
“…Participants were recruited from 2011 to 2016 as part of the Aging in a Community Environment Study 19 with details described in prior work. 20 Participants of any gender or race, aged 60-85, were recruited if they met the diagnostic criteria 6 of MCI. In brief, MCI was defined by the presence of subjective cognitive complaint and objective cognitive impairment, but with no loss of functional independence.…”
Section: Participantsmentioning
confidence: 99%